Oral Oncoprevention by Phytochemicals - A Systematic Review Disclosing the Therapeutic Dilemma - Sujana Mulk Bhavana (Advanced Pharmaceutical Bulletin, 2014)
The aim of this article is to emphasize and focus on the preclinical and clinical update on phytochemicals and their role in prevention of oral carcinogenesis. Accordingly, the literature search was made following database: Embase, Medline, Science Citation index, NIH public access, pubmed and Cochrane Database of systematic reviews. Several internet websites were also searched to access publications from major phytochemical research sites and relevant information was obtained with regards to each plant chemical. The authors also spotted different list servers through wignet.com, Stanford cancer research etc: The data base search was made from the inception to 1988 and updated till 2013. A systematic method was obtained for literature search and data collection was critiqued. 60 articles were searched, among which there were only 6 systematic reviews on phytochemicals regarding oral carcinogenesis. Additional articles were obtained on phytochemicals and their mechanism of action in other cancers, which were regarded as background material. The studies done by various authors on each phytochemical has been briefly emphasized.